Proceedings of the 20th International Conference on Distributed Computing and Networking 2019
DOI: 10.1145/3288599.3288601
|View full text |Cite
|
Sign up to set email alerts
|

Distributed symmetry-breaking with improved vertex-averaged complexity

Abstract: We study the distributed message-passing model in which a communication network is represented by a graph G = (V, E). Usually, the measure of complexity that is considered in this model is the worst-case complexity, which is the largest number of rounds performed by a vertex v ∈ V .While often this is a reasonable measure, in some occasions it does not express sufficiently well the actual performance of the algorithm. For example, an execution in which one processor performs r rounds, and all the rest perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In the current paper we investigate yet another distributed setting, namely, the Sleeping Setting. Several variants of this setting have attracted the attention of researchers recently [5,8,10,13,18,22]. The particular setting and complexity measure we consider in this paper were introduced by Chatterjee, Gmyr and Pandurangan [8] in PODC '20. This sleeping setting is similar to the standard distributed LOCAL setting [24], but has an additional capability, as follows.…”
Section: Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current paper we investigate yet another distributed setting, namely, the Sleeping Setting. Several variants of this setting have attracted the attention of researchers recently [5,8,10,13,18,22]. The particular setting and complexity measure we consider in this paper were introduced by Chatterjee, Gmyr and Pandurangan [8] in PODC '20. This sleeping setting is similar to the standard distributed LOCAL setting [24], but has an additional capability, as follows.…”
Section: Our Resultsmentioning
confidence: 99%
“…An important efficiency measurement in this setting is the vertex-averaged awake complexity. This setting was further studied by Barenboim and Tzur [5], who obtained various symmetry-breaking algorithms with improved vertex-averaged complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Several variants of the sleeping setting were studied recently [7,8,9,11,12,13]. The particular setting and complexity measurement we consider in this paper were introduced by Chatterjee, Gmyr and Pandurangan [8] in PODC'20.…”
Section: Previous Workmentioning
confidence: 99%
“…The setting is studied under several models, more known among them are the LOCAL model and the CON GEST model. In recent years the sleeping model (or some variation thereof) came to the focus of researchers [7,8,9,11,12,13,6]. In this model nodes can go into a sleep state in which they spend no energy but at the same time cannot receive or send messages, nor can they perform internal computations.…”
mentioning
confidence: 99%
“…Recently Barenboim and Tzur [6] showed that MIS can be solved in O(a + log * n) rounds under node-averaged complexity deterministically, where a is the arboricity of the graph. It is a open question whether one can design an algorithm with O(1) (or even o(log n)) node-averaged round complexity in the traditional model for general graphs (which can have arboricity as high as Θ(n)).…”
Section: Mis In O(1)-rounds Node Average Complexity?mentioning
confidence: 99%